Giant retrosternal goiter masquerading as, right posterior mediastinal mass: a rare case report - Punjani, Jaykumar N.; Shah, Kesha K.; Haridas, Arun Kumar (International Surgery Journal, 2019)
Complete mediastinal plunging thyroid gland is a rare entity, accounting for 1% of all mediastinal tumours, particularly posterior mediastinal tumour much more rare. We would like to present, a 30-year-old lady presented to ENT department with neck swelling and its further investigation shown to be giant posterior mediastinal mass. Thyroid function tests were normal. CT scans of the neck and chest revealed a large right mediastinal mass compressing the trachea from the right side and extending to the superior part of the posterior mediastinum with enlarged right thyroid gland in the cervical position. Midline extended sternotomy was done for complete surgical excision of the mass along with right hemi thyroidectomy. It was well circumscribed, capsulated, multinodular firm inconsistency, and vascular. Histopathology revealed thyroid tissue negative for malignancy. Giant plunging thyroid in the mediastinum is very rare. It should be differentiated from other mediastinal mass. The plunging goiter in posterior mediastinum is surgically challenging. Transsternal surgical removal is the treatment of choice in such cases.